Peranan Guru PAI (Akidah Ahklak) Dalam Pembinaan Ahklak Siswa Di Mts N 1 Buton Tengah - Usman Usman (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
This study uses a qualitative method. Data collection techniques were carried out by in-depth interviews, participant observation and documentation. Data were analyzed using an interactive model consisting of collecting data (data collection), reducing data (data reduction), presenting data (data display), and concluding (conclusion). Checking the validity of the data is done by testing the credibility, transferability, dependability, and confirmability. This study also aims to find: (1) the role of PAI teachers (aqidah morals) in fostering student morals, (2) What are the driving factors in fostering student morals at MTs N 1 Central Buton, (3) What are the inhibiting factors in fostering student morals in MTs N 1 Central Buton. The results of this study indicate that: (1) the role of PAI teachers (aqidah morals) in fostering student morals at MTs N 1 Buton Tengah has shown a good attitude in accordance with Islamic teachings and applies what they get from the explanations given by the teacher at class during the learning process. (2) The driving factors in fostering student morals at MTs N 1 Central Buton are; parental factors and exemplary factors, (3) while the inhibiting factors in fostering student morals at MTs N 1 Central Buton namely; different family factors and friend factors.